Associations between Vitamin D and Cardiovascular Disease Risk Factors in African Americans Are Partly Explained by Circulating Adipokines and C-Reactive Protein: The Jackson Heart Study. Issue 12 (26th October 2016) - Khan, Rumana J; Gebreab, Samson Y; Riestra, Pia; Sims, Mario; Gaye, Amadou; Xu, Ruihua; Davis, Sharon K
Abstract: Background: Although it is recognized that vitamin D deficiency is associated with cardiovascular disease (CVD) risk factors, and is more common in African Americans (AAs), the pathologic mechanisms by which vitamin D may influence these risk factors are poorly understood. Objectives: We explored the association between vitamin D status, as reflected by serum 25-hydroxyvitamin D [25(OH)D] concentrations, and CVD risk factors including mean arterial pressure (MAP), fasting plasma glucose (FPG), plasma HDL cholesterol, and waist circumference (WC) in adult AAs. We also tested whether plasma C-reactive protein (CRP), adipokines (adiponectin and leptin), and aldosterone mediated the associations between 25(OH)D and these risk factors. Methods: Data on 4010 (63.8% women; mean age: 54.0 y) individuals from the Jackson Heart Study were analyzed. Multivariable linear regression models were used to examine the associations of 25(OH)D with CVD risk factors. We used path analysis and bootstrapping methods to quantify and test the share of these associations that was statistically explained by each of the mediators by decomposing the associations into direct and indirect effects. Results: Serum 25(OH)D concentrations were inversely associated with WC, FPG, and MAP and were positively associated with HDL cholesterol in multivariable analysis. A nearly 20% effect of 25(OH)D on MAP was masked by aldosterone (total indirect effect: β = 0.01, P < 0.05). Approximately 23% of the effect of 25(OH)D on WC (β = −0.03, P < 0.05) and ∼9% of the effect of 25(OH)D on FPG (β = −0.02, P < 0.05) were mediated through CRP, adiponectin, and leptin together. A 23% share of the association between 25(OH)D and HDL cholesterol was mediated by adiponectin alone (β = 0.03, P < 0.05). Conclusions: Our findings suggest that the associations between vitamin D status and CVD risk factors in AAs are partially mediated through circulating adipokines and CRP. More evidence, however, is required from longitudinal and randomized controlled studies to validate our findings.